Security of E-Banking transactions in Bangladesh: Does it need more importance from COVID-19 perspective? (IIUC Business Review, 2021)
Electronic banking service has grown in Bangladesh since 2001. Now, it has become most suitable and convenient fund transfer method in COVID-19 pandemic situation. The security risk issue is the most vital in the e-banking fund transfer. A survey was conducted where the risk factors were measured on five-point Likert scale by 200 bankers and customers in the pandemic period through phone and E-mail. After necessary modification and correction of collected data, descriptive statistics, Cronbach’s Alpha, Kolmogorov-Smirnov test, Shapiro-Wilk test, Mann Whitney U test and Kruskal-Wallis H test were conducted in IBM SPSS Statistics 20 and MS Excel 2010to test the hypothesis of the risk factor. Result shows the highest banking transaction risk factor is Account Information Security and lowest banking transaction risk factor is Double Check identity from the perspective of customers. The result also shows that less than 2 years experiences of e-banking are significantly more satisfied than the risk factor of 2 years to 6 years and more than 6 years e-banking experiences.IIUC Business Review Vol. 10, Dec. 2021 pp. 9-24